Indirect Holography Breast Cancer Detection System (IH-BCDS) Using VORD - Biabani, Sardar Asad Ali; Shafie, Emad; Khozium, Mohamed Osama (European Scientific Journal, ESJ, 2017)
Microwave Imaging is a prominent technique in current imaging modalities for breast cancer detection and its treatment, primarily due to the significant dielectric property contrast between normal and malignant breast tissues. This study describes how VORD Viewpoint-Oriented Requirement Definition (VORD) method is used to examine patients for early detection of cancer by microwave imaging by realizing the existence of multiple perspectives by terminating differences in the demands of stakeholders. The proposed system in this paper is based on microwave imaging by Indirect Holography for Breast Cancer Detection System (IH-BCDS) using Viewpoint-Oriented Requirement Definition (VORD) method. The suggested approach for developing such system is to investigate the possibility of detecting tumors at an early stage by utilizing VORD as analysis tool which is an activity oriented framework for IH-BCDS requirement elicitation. If the system gets implemented successfully, it can play a vital role in detecting the tumor at an early stage by helping a medical specialist in decision making to diagnose the patient.